The Designer’s Eye: Ancient Spanish Ballads, Poetry, and the Rise of Decorative Design - Frankel, Nicholas (Romanticism and Victorianism on the Net, 2009)
AbstractIn 1841 John Murray published a sumptuously ornamented edition of John Gibson Lockhart’s Ancient Spanish Ballads. Murray’s new edition, printed using the very latest bookmaking technologies and pitched at a readership newly accustomed to paying exorbitant prices for book ornaments and illustrations, was radically different from the first edition of Lockhart’s ballads, which had appeared without accompanying ornament in 1823. Illustrated by the leading illustrators of the day and decorated throughout in multiple colors by the architect Owen Jones (who would go on to become famous as a Superintendent of the Great Exhibition and the author of The Grammar of Ornament), Murray’s edition represents a stunning departure in Victorian printing and a highpoint in mid-Victorian design generally. At the same time, it crystallizes a debate about the nature and application of artistic design that was beginning to emerge in the early years of Victoria’s reign and that would erupt with maximum vigor ten years later in the confrontation between John Ruskin and the South Kensington School. The tension between flat, stylized design and what Ruskin was later to term “truth to nature” is already palpable in the conflict between illustrations and ornaments to Murray’s book. However, it was the involvement of Owen Jones that especially distinguished the volume, as it gave Jones the opportunity to demonstrate in a practical way ideas about design, color, and style that he would theorize fifteen years later in The Grammar of Ornament. Those ideas are especially resonant today, given recent work on the history of the book and the “bibliographic codes” of literature, since the effect of Jones’s work is to expose the textual condition of Lockhart’s poetry itself and to harness the eye as an active constituent in the act of reading. Fifty years before the work of William Morris at the Kelmscott Press, Jones and Murray showed Victorian readers that a printed book might be a thing of real beauty and that poetry, no less than painting or architecture, is dependent on the perceptual structure of its textual vehicle.